Digital financial literacy, ease of use, and price value on cashless adoption generation z padang - Aulia Febrika; Maivalinda (UPI YPTK Journal of Business and Economics, 2026)
This study aims to examine the effect of digital financial literacy, ease of use, and price value on cashless payment adoption among Generation Z in Padang City. The rapid development of financial technology has shifted transaction behavior from cash-based systems to digital payment methods, making cashless transactions increasingly important. However, the level of adoption among Generation Z is still influenced by several factors related to user understanding, system usability, and perceived economic benefits. This study employs a quantitative approach using a survey method through questionnaire distribution. The sample consists of 96 respondents selected using purposive sampling. Data analysis was conducted using multiple linear regression with SPSS software. The results show that digital financial literacy, ease of use, and price value each have a positive and significant effect on cashless payment adoption. Furthermore, these variables simultaneously have a significant influence on adoption behavior. The coefficient of determination indicates that a substantial portion of adoption can be explained by the proposed model. These findings highlight the importance of improving financial knowledge, enhancing system usability, and providing economic incentives to increase the adoption of cashless payment among Generation Z.